2021
DOI: 10.1002/pssa.202000819
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric and Dielectric Properties of Hf0.5Zr0.5O2 Thin Film Near Morphotropic Phase Boundary

Abstract: Since the discovery of ferroelectric (FE) properties in HfO 2 -based materials, [1] numerous advantages, such as simple structures, strong binding energy between oxygen and transition metal ions, large bandgap (%5.3-5.7 eV), and compatibility with current complementary metal-oxide semiconductor technologies, led to extensive research that focused on potential diverse applications, such as FE memory, ferroelectric field-effect transistors (Fe-FETs), pyroelectric sensors, and energy harvesters. Meanwhile, from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Although the experimental data agree with equation (1) [9,19,20], this equation is only valid when domain nucleation and growth are suppressible and Landau-Ginzburg-based uniform switching occurs during polarization switching of HfO 2 samples [13,14]. Several groups have shown that the switching kinetics of the HfO 2 based ferroelectrics result from the nucleation and growth of domains [21][22][23][24][25].…”
Section: I According To the Landau Formula E Csupporting
confidence: 55%
See 1 more Smart Citation
“…Although the experimental data agree with equation (1) [9,19,20], this equation is only valid when domain nucleation and growth are suppressible and Landau-Ginzburg-based uniform switching occurs during polarization switching of HfO 2 samples [13,14]. Several groups have shown that the switching kinetics of the HfO 2 based ferroelectrics result from the nucleation and growth of domains [21][22][23][24][25].…”
Section: I According To the Landau Formula E Csupporting
confidence: 55%
“…The formation of the monoclinic phase (m-phase) was nonexistent for all devices, and the o/t phase characteristic peaks were observable. The o (111) and t (011) peaks were at 2θ°-30.4°a nd 30.8°, respectively [19,20]. As the T A increased, a left shift of o/t Bragg peak from 2θ°to 30.5°occurred (see inset of figure 2(b)), revealing the formation of polar o-phase and reduction of t-phase [19,20], which was in line with polarization evolution due to the annealing condition presented in figure 2(a).…”
Section: Resultsmentioning
confidence: 99%
“…A novel approach based on the existence of morphotropic phase boundaries (MPB) was recently developed. [281,283,[292][293][294][295] This approach introduced a substantial improvement in the dielectric properties of HfO 2 -based thin films. In fact, the discovery of ferroelectricity and anti-ferroelectricity in HfO 2 -ZrO 2 (HZO) solid solution thin films [246][247][248][249][250][251][252][253][254][255][256][257][258][259][260][261][262] paved the way for enhancing dielectric properties through MPB, which will be discussed later in Section 8.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…The ferroelectric O-phase is reported to have a lower dielectric constant than the antiferroelectric T-phase. [21,24] Measurements conducted far from the peaks in the C-V curve are less influenced by domain wall contributions [25] to the capacitance and provide a more reliable measure of the dielectric constant. In the present case, the majority O-phase ALD 250 °C sample has a lower dielectric constant than the majority T-phase ALD 200 °C sample for all cycling states, Figure 4a,b.…”
Section: Capacitance-voltage Measurementsmentioning
confidence: 99%